The combination of Shenhuang plaster and paclitaxel inhibits lung metastasis in breast cancer via modulation of the tumor microenvironment - Chen, Shiqi; Karekad, Maryam Mohammed Abbas; Liu, Ting; Ding, Bin; Wang, Rongyun; Sun, Qiuhua; Xu, Xiaohong; Shi, Yanan (Frontiers in Oncology, 2025)
BackgroundPaclitaxel (PTX) is a chemotherapeutic agent that is frequently used for breast cancer treatment, but it has been associated with promoting distant metastases, including to the lungs, liver, and bones. Shenhuang plaster (SHP), a traditional Chinese medicine, has shown potential for modulating the tumor microenvironment (TME). This study investigates whether a combination of SHP and PTX can enhance the anti-tumor efficacy of PTX and mitigate its pro-metastatic effects in a 4T1 breast cancer mouse model.MethodsFemale Balb/c mice were injected with 4T1 breast cancer cells and then divided into four treatment groups: control, PTX, SHP, and PTX+SHP. The combination of SHP and PTX was evaluated using bioluminescence imaging (BLI), histological analysis, and hematoxylin and eosin (HE) staining to assess lung metastasis. Flow cytometry was employed to analyze immune cell populations, including tumor-associated macrophages (TAMs), myeloid-derived suppressor cells (MDSCs), regulatory T cells (Tregs), and cytotoxic T cells (CD8+ and CD4+).ResultsSHP alone did not significantly inhibit lung metastasis but the combination of PTX and SHP led to a marked reduction in lung lesions, as confirmed by BLI and histological analysis. SHP improved the overall health of PTX-treated mice, reducing their body weight loss and mortality. Flow cytometry revealed that the combination therapy reduced the infiltration of M2 macrophages, MDSCs, and Tregs, while increasing the proportion of antitumor M1 macrophages, cytotoxic CD8+ T cells, and helper CD4+ T cells.ConclusionsThe combination of PTX and SHP has a synergistic effect, reducing lung metastasis and modulating immune cell populations within the TME. These results suggest that integrating traditional Chinese medicine with standard chemotherapy can enhance therapeutic efficacy and reduce adverse effects.